Oil and the Economy of Russia : From the Late-Tsarist to the Post-Soviet Period - Moser, Nat (BASEES/Routledge series on Russian and East European studies, 2017)
"This book examines the development of the Russian economy from tsarist times to the present through the lens of the oil industry. It considers the role of the state, business-state relations, foreign participation, enterprise performance and technology. Besides providing much rich detail on the changing nature of the oil industry, the book also puts forward important conclusions, including the fact that in the late nineteenth century private enterprise rather than the state was the principal driver of economic development, and that after the collapse of the Soviet Union incumbent managers were more effective in running their companies than financier entrants, whose main concern was short-term gain."--Provided by publisher